Dystopia in the contemporary Arabic novel: a reading of *In the Beginning Was the Word* by Amal Bouchareb - boukhalfa, brahim (El Omda in Linguistics and Discourse Analysis, 2024)
The dystopian novel in the West emerged as a response to postmodern philosophies, characterized by a pessimistic tendency and a nihilistic view of existence, in the context of savage capitalism and authoritarian political regimes. This type of novel aimed to deconstruct the utopian thinking of modern philosophies, which inherited an Enlightenment project rooted in humanist and idealistic values. With the collapse of grand narratives, Western thought shifted toward the opposite of utopia, a transformation clearly reflected in the novel form. Later, the dystopian novel was transferred into Arab culture through cultural openness, and we began to read dystopian narratives expressing deep crises in Arab societies marked by authoritarian regimes that deprived their peoples of many rights and opportunities. Among these works, this article examines In the Beginning Was the Word by Amel Bouchareb, which expresses the state of despair, misery, and hardship reached by Algerian society following the failure of the peaceful transition project toward democracy.